1995
DOI: 10.1103/physrevlett.74.499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Hyperfine Interaction on Orbital Electron Capture

Abstract: Electron capture from an unfilled atomic s orbital is investigated theoretically.Analyses are carried out for two simple situations, a mirror transition of a nucleus with a nucleon in an outer sl/2 state and a Gamow-Teller transition decreasing the nuclear spin by one unit. It is shown that the hyperfine interaction between electron and nuclear spins has a great infIuence on the rate of electron capture at temperatures small compared to the hyperfine splitting. The possibility of inducing electron capture with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 14 publications
5
36
0
Order By: Relevance
“…This means that the capture rate is dominated by K-shell electrons since λ K /λ L ≈ 2 3 = 8, λ K /λ M ≈ 3 3 = 27, etc. Possible deviations from this simple assumption have been predicted for highly-charged atoms [16]. It is clear that fully-ionized 7 Be ions are stable.…”
Section: Half-lives Of 7 Be In Different Atomic Charge Statesmentioning
confidence: 93%
See 3 more Smart Citations
“…This means that the capture rate is dominated by K-shell electrons since λ K /λ L ≈ 2 3 = 8, λ K /λ M ≈ 3 3 = 27, etc. Possible deviations from this simple assumption have been predicted for highly-charged atoms [16]. It is clear that fully-ionized 7 Be ions are stable.…”
Section: Half-lives Of 7 Be In Different Atomic Charge Statesmentioning
confidence: 93%
“…The decay of 10 MeV/nucleon 11 Be into 10 Be + p would produce protons at a maximum angle of 9.9 degrees, with energies between 7 MeV and 13.5 MeV. The α particles from the decay of 16 N would, in the region of interest for astrophysics, by emitted within a cone of 8 degrees with energies between 30 MeV and 50 MeV. Detection of the emitted light ions could take place in charged-particle detectors, which would provide energy and trajectory information.…”
Section: In-flight Beta-decay Of Light Exotic Nucleimentioning
confidence: 99%
See 2 more Smart Citations
“…The directed neutrino beam can be switched and modulated by manipulation of the magnitude and direction of the magnetic field. It was also shown that electron capture beta-decay in hydrogen-like ions is extremely sensitive to the hyperfine interaction [4] [5] [6] [7] [8]. In fact, the decay from one of the hyperfine states can be completely forbidden.…”
Section: Introductionmentioning
confidence: 99%